Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 82265 by Ali Yousafzai last updated on 19/Feb/20

factorize:  (x+1)(x+2)(x+3)(x+6)−3x^2

factorize:(x+1)(x+2)(x+3)(x+6)3x2

Answered by MJS last updated on 19/Feb/20

=x^4 +12x^3 +44x^2 +72x+36=       [x=t−3]  =t^4 −10t^2 +24t−27=  =(t^2 −αt−β)(t^2 +αt−γ)=         comparing factors leads to        { ((α^2 +β+γ−10=0)),((αβ−αγ+24=0)),((βγ+27=0)) :}       ⇒ α=2∧β=−3∧γ=9    =(t^2 −2t+3)(t^2 +2t−9)=  =(x^2 +4x+6)(x^2 +8x+6)=  =(x+4−(√(10)))(x+4+(√(10)))(x+2−i(√2))(x+2+i(√2))

=x4+12x3+44x2+72x+36=[x=t3]=t410t2+24t27==(t2αtβ)(t2+αtγ)=comparingfactorsleadsto{α2+β+γ10=0αβαγ+24=0βγ+27=0α=2β=3γ=9=(t22t+3)(t2+2t9)==(x2+4x+6)(x2+8x+6)==(x+410)(x+4+10)(x+2i2)(x+2+i2)

Answered by behi83417@gmail.com last updated on 19/Feb/20

(x+1)(x+6)=x^2 +7x+6  (x+2)(x+3)=x^2 +5x+6  ⇒^(x^2 +6=t) (t+5x)(t+7x)=t^2 +12tx+35x^2   ⇒p=t^2 +12tx+32x^2   △=144x^2 −4×32x^2 =16x^2   ⇒t=((−12x±4x)/2)=−8x,−4x  ⇒p=(x^2 +4x+6)(x^2 +8x+6)  ⇒p=[(x^2 +4x+4)+2][(x^2 +8x+16)−10]=  =[(x+2)^2 −2i^2 ][(x+4)^2 −10]=  =(x+2+i(√2))(x+2−i(√2))(x+4+(√(10)))(x+4−(√(10))) .

(x+1)(x+6)=x2+7x+6(x+2)(x+3)=x2+5x+6x2+6=t(t+5x)(t+7x)=t2+12tx+35x2p=t2+12tx+32x2=144x24×32x2=16x2t=12x±4x2=8x,4xp=(x2+4x+6)(x2+8x+6)p=[(x2+4x+4)+2][(x2+8x+16)10]==[(x+2)22i2][(x+4)210]==(x+2+i2)(x+2i2)(x+4+10)(x+410).

Terms of Service

Privacy Policy

Contact: info@tinkutara.com